Postcolonialism and translation: an analysis of the novel Half a Life and its translation to Portuguese - Ruffini, Mirian (2019)
The publication of translations of postcolonial literary works is increasingly gaining space in the Brazilian publishing market. In this article, the articulation between Translation Studies and Postcolonial Studies is sought through the analysis of the post-colonial novel Half a Life, by V.S. Naipaul, and its translation to Brazilian Portuguese, entitled Meia Vida. Discussions of ideological aspects in the translation of postcolonial texts and the very choice of what is translated and by whom are questions raised by the text, as well as the challenges of translating postcolonial literary texts. Finally, it is discussed how the postcolonial discourse of the original work is transmitted through translation, ascertaining possible suppression or maintenance of the postcolonial tone of the original work in the translated work.